The Relationship between locus of control based on King’s theory of goal attainment and nurses’ performance in hospitals: A cross-sectional study - Nur Eka Djihan Dinah; Wahyu Endang Setyowati; Muh Abdurrouf (Lentera Perawat, 2026)
Background: Nurses’ performance is a central determinant of hospital service quality, patient safety, and continuity of care. In demanding clinical environments, performance is influenced not only by organizational conditions but also by psychological factors, including locus of control. Within the perspective of King’s Theory of Goal Attainment, locus of control is relevant because nurses’ beliefs about personal control may shape communication, responsibility, decision making, and the achievement of care goals. Objective: This study aimed to examine the relationship between locus of control based on King’s Theory of Goal Attainment and nurses’ performance in hospitals. Methods: This study employed a quantitative correlational design with a cross-sectional approach. The study was conducted at Weda Hospital, Central Halmahera Regency, North Maluku, Indonesia, in September 2025. The population consisted of 145 nurses working in the Male Internal Medicine Ward and Neurology Ward. A total of 117 respondents were selected using simple random sampling. Locus of control was measured using a 16-item questionnaire, while nurses’ performance was assessed using a 15-item questionnaire. Data were analyzed using univariate statistics, cross-tabulation, and Pearson correlation analysis. Results: Most respondents were aged 36–45 years (29.9%), female (72.6%), held a bachelor’s degree (66.7%), and had 21–30 years of work experience (32.5%). Internal locus of control was the most common category (45.3%), while low nurses’ performance was slightly more frequent (37.6%) than high performance (35.9%). Cross-tabulation showed that nurses with external locus of control were predominantly in the low-performance category (60.5%), whereas those with internal locus of control were predominantly in the high-performance category (52.8%). Pearson correlation analysis revealed a statistically significant positive relationship between locus of control and nurses’ performance (r = 0.479; p < 0.001; 95% CI: 0.32–0.62). Conclusion: Locus of control was significantly associated with nurses’ performance in the hospital setting. Nurses with stronger internal control beliefs tended to demonstrate better performance. These findings suggest that strengthening nurses’ personal agency, responsibility, and goal-oriented professional attitudes may contribute to improving nursing performance and the quality of hospital care.